1993
DOI: 10.1111/j.1476-5381.1993.tb13803.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ATP and α,β‐methylene‐ATP on cytosolic Ca2+ level and force in rat isolated aorta

Abstract: 1 The effects of a non-selective P2-receptor agonist ATP and a selective P2x-receptor agonist a,pmethylene-ATP on intracellular free Ca2+ level ([Ca2+]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…The latter observations support the view that the increase in IP3 content elicited by 1 mM ATP might not be sufficient to elicit the release of Ca2+ from internal source, whereas it was sufficient when the arteries were exposed to 3 mm ATP. The above data are in accordance with those reported by different authors within either isolated aorta or aortic smooth muscle cells of the rat (Nambi, Hsiao-Ling & Nambi, 1990;Kitajima, Ozaki & Karaki, 1993). However, the present results contrast with those in rat portal vein showing that ATP released Ca2+ from intracellular stores by a mechanism that involved Ca2+ entry (Pacaud, Gregoire & Loirand, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…The latter observations support the view that the increase in IP3 content elicited by 1 mM ATP might not be sufficient to elicit the release of Ca2+ from internal source, whereas it was sufficient when the arteries were exposed to 3 mm ATP. The above data are in accordance with those reported by different authors within either isolated aorta or aortic smooth muscle cells of the rat (Nambi, Hsiao-Ling & Nambi, 1990;Kitajima, Ozaki & Karaki, 1993). However, the present results contrast with those in rat portal vein showing that ATP released Ca2+ from intracellular stores by a mechanism that involved Ca2+ entry (Pacaud, Gregoire & Loirand, 1994).…”
Section: Discussionsupporting
confidence: 93%
“…rat aorta and large mesenteric arteries, there is a reduced sensitivity of contractions to α,β-meATP [28, 47]. However, P2X 1 receptor immunoreactivity is detected in these vessels (albeit at somewhat reduced levels, as found in this study), and α,β-meATP has been shown to evoke transient rises in intracellular calcium with an EC 50 of <1 µ M from acutely dissociated aortic smooth muscle [60]. In addition, transient P2X 1 receptor-like currents have been recorded from large mesenteric artery cells [Gitterman and Evans, unpubl.…”
Section: Discussionmentioning
confidence: 45%
“…Ths type of dissociation may be due to the Ca2" sensitzing effect of neurotransmitters (Karaki, 1989). Furthermore, it has been shown that the initial transient increase in the fura-2 signal is not always coupled to contraction (Sakata et al, 1989;Kitajima et al, 1993). This type of dissociation may be due to the 'non-contractile' Ca2+ compartment.…”
Section: Discussionmentioning
confidence: 99%